2011
DOI: 10.1021/nl2019382
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of a Noncatalytic Growth Regime for GaAs Nanowires

Abstract: We identify a new noncatalytic growth regime for molecular beam epitaxially grown GaAs nanowires (NWs) that may provide a route toward axial heterostructures with discrete material boundaries and atomically sharp doping profiles. Upon increase of the As/Ga flux ratio, the growth mode of self-induced GaAs NWs on SiO(2)-masked Si(111) is found to exhibit a surprising discontinuous transition in morphology and aspect ratio. For effective As/Ga ratios <1, in situ reflection high-energy electron diffraction measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 50 publications
(114 reference statements)
12
141
2
Order By: Relevance
“…38 Such a transition from VLS to non-VLS conditions was observed to depend on the As/Ga ratio for GaAs NWs on Si. 36 In all cases the incubation time is expected to increase with the catalyst size, which is indeed a trend which is suggested by the catalyst size dependence on final NW length (data in Fig. 5, and the heuristic dependence used in the overall fits).…”
Section: Discussionsupporting
confidence: 60%
“…38 Such a transition from VLS to non-VLS conditions was observed to depend on the As/Ga ratio for GaAs NWs on Si. 36 In all cases the incubation time is expected to increase with the catalyst size, which is indeed a trend which is suggested by the catalyst size dependence on final NW length (data in Fig. 5, and the heuristic dependence used in the overall fits).…”
Section: Discussionsupporting
confidence: 60%
“…Precise control of the axial and radial growth rates of GaAs and AlGaAs was achieved by varying the temperature and III/V flux ratio during MBE growth. Initially, a seed GaAs NW core was synthesized in a self-catalysed (Ga droplet mediated) vapour-liquidsolid growth mode 23 . The NWs thus produced have lengths in the range from 11 to 16 mm and a diameter of 80±5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The GaAs-AlGaAs core-shell NWs were grown using solid source MBE on Si(111) substrates that were thermally oxidized to produce a 20 ± 1-nm-thick SiO 2 mask layer. Before growth, the oxide was thinned using an aqueous, dilute NH 4 -HF solution to produce a B2-nm-thick SiO 2 layer containing pinholes to the Si(111) substrate, which act as nucleation sites for NW growth 23,24,45,46 . The prepared substrates were then transferred into a Gen II MBE system and held at 700°C for 20 min to remove surface contaminants before being cooled to the nominal growth temperature of 610°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Nevertheless, molecular beam epitaxy (MBE) can provide accurate control over the growth parameters for high-quality nanorod heterostructures with very clean and sharp interfaces using various in situ monitoring techniques, such as reflection high electron energy diffraction (RHEED). 12,13 Realizing the advantage of MBE growth method, Zhuang et al demonstrated In droplet-assisted growth of InAs nanorods on mechanically exfoliated graphite flakes using MBE. 14 However, it is important to develop catalyst-free MBE growth method of nanorods on graphene, as this growth method is known to be the best method to produce ultrapure nanorods with homogeneous composition, which are essential building blocks for future nanorod-based devices.…”
Section: Introductionmentioning
confidence: 99%